American foreign policy - Jentleson, Bruce W. (W.W. Norton, 2007)
American Foreign Policy helps students approach these issues by applying a consistent critical framework throughout the text, emphasizing both the strategic and political aspects of foreign policy decision-making. With new readings and pedagogy in the text and a new Web site for study and review, the Third Edition is an unparalleled introduction to U.S. foreign policy amidst the challenges of terrorism, the war in Iraq, the Darfur crisis, globalization, democratization, and other timely issues